Interpretation of Urodynamic Studies A Case Study-Based Guide - Oh, Seung-June (Springer Singapore, 2018)
This book is a comprehensive guide to lower urinary tract dysfunction that draws extensively on actual urodynamic traces and patient cases to ensure that the imparted knowledge will be readily transferable to clinical practice. The impressive collection of clinical cases is used to illustrate basic concepts of lower urinary tract function and to document urodynamic findings and typical patterns in a wide range of commonly encountered conditions. In addition, attention is drawn to frequent pitfalls and artifacts. Readers will be able to assess their skill in reaching the correct diagnostic conclusion in each case, as in addition to the urodynamic trace a full set of information is provided on aspects such as patient history, physical examination, voiding diary, laboratory examination, imaging studies, and cystourethroscopy, thereby directly simulating real-life clinical practice. The presented cases are drawn from the large clinical database that Professor Seung-June Oh has prospectively accumulated during the past 16 years of clinical practice. The book will be invaluable for residents and other practitioners and will also be of interest for medical students.